EDUCATIONAL POTENTIAL OF VIDEO GAMES: WORLDVIEW AND METHODOLOGICAL FOUNDATIONS - Horban, Olexander (Educological discourse, 2019)
The article reveals the essence of the video game as a special phenomenon of the social reality of a modern man. The idea of the need to develop a qualitatively new strategy for the development of the educational space based on the active involvement in the educational process of the latest communication technologies on video game platforms is substantiated. It has been found that human activity is intertwined with the game or includes certain game elements of the initial formation of society. The game performs a particular educational function, which simulates certain situations and provides basic practical skills. In this case, the game process teaches through entertainment, brings up with ease, which sometimes lacks a classical education. Discovered educational potential and analyzed the educational prospects of video games. Notes the use of video games in the educational process in three areas: educational games, gamification of education and learning based on the game (Game Based Learning). Educational games are games that are developed and used in training. They combine the characteristic elements of video games - multimodalism, interactivity, specific organization of the game situation, narrative and social goals. Gamification in education involves the use of a “like in-game” rule system, the experience and role of the player to shape the student’s behavior. At the core of gamification is the idea of implementing a gaming approach in order to make learning more fun. Game Based Learning (GBL) is a form of learning that is used to encourage students to learn during the game and make learning more interesting by adding fun to the learning process. Video games in this case are attracted to the classical educational process as a model, example, or element of reward. The conclusion is made about the prospects of attracting video games to the educational process as innovative methodological tools that can generate relevant educational and professional competence.